Glucagon for the treatment of symptomatic β blocker overdose. Issue 3 (1st May 2003) - Boyd, R; Ghosh, A
Abstract : A short cut review was carried out to establish whether the intravenous glucagon can support blood pressure in β blocker overdose. A total of 51 papers were found using the reported search, of which six presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.